EVALUATION OF ROOT AND LEAF OF ABUTILON THEOPHRASTI MEDIK FOR ANTIFUNGAL ACTIVITY - Hassan, Musheerul; Habib, Huma; Kausar, Nasreen; Ma, Zargar; Mir, Reyaz Ahmad (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT The investigation was aimed to carry out the antifungal activities of the methanol and aqueous extracts of Abutilon theophrasti against four fungal strains (Microsporum gypseum, Penicillium spp., Fusarium spp., Aspergillus spp.). Antifungal activity of the extracts was determined by the disc diffusion method against various fungi with soubred dextrose agar as media. Methanolic extracts of A. theophrasti showed promising antifungal activity compared to aqueous extracts against selected fungal species. Methanolic extract of leaf displayed the highest activity with zone of inhibition 14 mm against Penicillium spp. which were totally concentration dependent; however, a poor activity was seen in aqueous extracts. Methanolic extracts of root displayed good antifungal activity, while as no activity was seen in aqueous extracts of root. The results obtained in the study show that methanolic leaf extracts possess phytoconstituents with potent antifungal activity. Keywords: Abutilon, Methanol, Rhizopus, Penicillium.